Deserving Desire : Women's Stories of Sexual Evolution - Montemurro, Beth, 1972- (Book collections on Project MUSE., 2014)
Women experience considerable changes in their bodies, lives, and identity between the ages of twenty and seventy, including marriage, motherhood, the dissolution of relationships, and menopause, all of which often impact sexuality. In Deserving Desire, Beth Montemurro takes a wide-ranging look at the evolution of women's sexuality over time, with a specific focus on the development of sexual subjectivity-that is sexual confidence, agency, and a sense of entitlement to sexual desire. Detailed stories of the ninety-five women in this study explore how they become more comfortable with their bodies.